Oxygen reduction catalysts and their applications
Patent Information
- Application Number
- JP2025062735
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-04-04
- Publication Date
- 2026-10-16
Smart Images

Figure 2026169064000001 
Figure 2026169064000002 
Figure 2026169064000003
Abstract
Description
Technical Field
[0001] The present specification relates to an oxygen reduction catalyst and use thereof.
Background Art
[0002] Organonitrogen compounds added to catalyst metals used in fuel cells and water electrolysis systems are known to improve the activity of the oxygen reduction reaction in catalysts and increase the power generation efficiency of fuel cells. Examples of such organonitrogen compounds include melamine-formaldehyde polymers obtained by polymerizing a monomer having an aldehyde group (Patent Document 1).
Prior Art Documents
Patent Documents
[0003]
Patent Document 1
Summary of Invention
Problem to be Solved by the Invention
[0004] However, since melamine has three amino groups that serve as polymerization starting points, melamine-formaldehyde polymers are three-dimensionally crosslinked. For this reason, it has been found that melamine-formaldehyde polymers tend to deposit thickly on the surface of the catalyst metal, which may inhibit the supply of reaction substrates to the catalyst metal.
[0005] The present specification provides a technique that contributes to maintaining the oxygen reduction activity of a catalyst metal by adjusting the three-dimensional crosslinking of a melamine-formaldehyde polymer added to an oxygen reduction reaction catalyst.
Means for Solving the Problem
[0006] This disclosure relates to an oxygen reduction catalyst. The oxygen reduction catalyst comprises a catalytic metal having oxygen reduction reaction activity, and a modified layer containing a copolymer or cation thereof having structural units derived from melamine, structural units derived from formaldehyde, and structural units derived from one or two amino group-containing compounds. It is equipped with.
[0007] According to this oxygen reduction catalyst, the modified layer contains the copolymer. Since the amino group-containing compound has one or two amino groups, it does not form three-dimensional crosslinks when it reacts with formaldehyde. Therefore, three-dimensional crosslinking between melamine and formaldehyde is suppressed in the copolymer. As a result, deposition of the modified layer is suppressed, and the inhibition of the supply of the reaction substrate to the catalyst metal is suppressed or avoided. [Modes for carrying out the invention]
[0008] The oxygen reduction catalysts disclosed herein may further include the following embodiments. In another embodiment of the oxygen reduction catalyst, the amino group-containing compound is urea and / or benzoguanamine. This effectively suppresses three-dimensional crosslinking of the copolymer.
[0009] Another embodiment of the oxygen reduction catalyst is such that the molar ratio of structural units derived from the amino group-containing compound to structural units derived from melamine in the copolymer is 1.0 or less. This allows, for example, three-dimensional crosslinking of the copolymer to be appropriately suppressed, thereby allowing the oxygen reduction activity of the catalyst metal to be fully exhibited.
[0010] Furthermore, the disclosure herein may also be a cathode for a fuel cell, comprising the oxygen reduction catalyst. A fuel cell comprising the cathode may also be provided.
[0011] Furthermore, the disclosures herein may also include an anode for a water electrolysis system, comprising the oxygen reduction catalyst. Or, a water electrolysis system comprising the anode.
[0012] The following describes in detail various embodiments of the oxygen reduction catalyst (hereinafter also simply referred to as the catalyst) disclosed herein.
[0013] The oxygen reduction catalysts disclosed herein may be for fuel cells such as PEFCs, or for water electrolysis systems. The catalysts disclosed herein may be used in the cathode of a fuel cell, in the anode of a fuel cell, in the anode of a water electrolysis system, or in the cathode of a water electrolysis system.
[0014] The oxygen reduction catalysts disclosed herein may take the form of, for example, a catalyst ink, or a layered form as a so-called electrode. A binder, as described later, may be used as needed.
[0015] (Oxygen reduction catalyst) The oxygen reduction catalyst disclosed herein comprises a catalytic metal and a modified layer containing a copolymer or cation thereof having structural units derived from melamine, structural units derived from formaldehyde, and structural units derived from one or two amino group-containing compounds. These elements will be described below. Note that the cation of the copolymer includes cases where a basic functional group in the copolymer dissociates and ionizes, forming a salt with an organic acid or inorganic acid.
[0016] (Catalytic metal) The catalytic metal included in the catalyst is not particularly limited as long as it has oxygen reduction activity. For example, catalytic metals include platinum, ruthenium, iridium, rhodium, palladium, osnium, tungsten, lead, iron, chromium, cobalt, nickel, manganese, vanadium, molybdenum, gallium, aluminum, lanthanum, cerium, praseodymium, neodymium, samarium, gadolinium, and yttrium. One or more of these metals can be used in combination. Furthermore, the catalytic metal may be an oxide, nitride, sulfide, or phosphide, and one or more of these oxides can be used in combination.
[0017] The catalyst metal may preferably be one or more selected from platinum, platinum alloys, and platinum-containing composites. Examples of metals other than platinum included in platinum alloys and platinum-containing composites include ruthenium, iridium, rhodium, palladium, osnium, tungsten, lead, iron, chromium, cobalt, nickel, manganese, vanadium, molybdenum, gallium, aluminum, lanthanum, cerium, praseodymium, neodymium, samarium, gadolinium, and yttrium, and two or more of these metals may be included. The elemental ratio of metals other than platinum in the platinum alloy is not particularly limited and may be 0.11 to 50 atm%.
[0018] Such catalytic metals typically exist in a particulate form, and their average particle size is not particularly limited, but is, for example, between 1 nm and 100 nm.
[0019] The catalyst metal may be supported on a carrier. The carrier can be one or more selected from carbon and oxides. Examples of carbon include conductive carbon, carbon black (acetylene black, Ketjen black, channel black, roller black, disc black, oil furnace black, gas furnace black, lamp black, thermal black, and VULCAN® carbon), activated carbon, graphite, glassy carbon, graphite, graphene, carbon fiber, carbon nanotubes, carbon nitride, carbon sulfide, and carbon phosphide, and two or more of these can be used in combination. Examples of oxides include titanium oxide, niobium oxide, tin oxide, tungsten oxide, and molybdenum oxide, which can be used one or more in combination.
[0020] The carrier may be primary particles or secondary particles. The average particle diameter of the primary particles is not particularly limited, but for example, it is between 5 nm and 500 nm.
[0021] (modification layer) The modification layer is provided on the surface of the catalyst metal in order to accelerate the oxygen reduction activity of the catalyst metal. The modification layer contains a copolymer (hereinafter also simply referred to as the copolymer) having a structural unit derived from melamine, a structural unit derived from formaldehyde, and a structural unit derived from one or two amino group-containing compounds, or a cation thereof. The cation includes a cation formed by dissociation of a basic functional group contained in the copolymer, and a case where the cation forms a salt with an organic acid or an inorganic acid.
[0022] (Copolymer) The copolymer contained in the modification layer is not particularly limited, as long as it has an activity of promoting the oxygen reduction activity by the catalyst metal. The copolymer may be used alone or in combination of two or more kinds. The copolymer at least has a structural unit derived from melamine represented by the following formula (I).
[0023]
Chemical Formula
[0024] Further, the polymer may have a structural unit derived from a melamine derivative represented by the following formula (II) in place of melamine.
[0025]
Chemical Formula
[0026] In formula (II), R1, R2, and R3 are, respectively, a hydrogen atom, a halogen atom, or a nitrile group, an amide group, an imine group, an amino group, a thiol group, a hydroxyl group, a sulfo group, a carboxylic acid group, a phosphoric acid group, a ketone group, an aldehyde group, an ester group, an alkoxy group, a phenol group, a cyclopentyl group, a cyclohexyl group, a C1-C10 alkylamino group, a C1-C10 alkyl sulfonic acid group, a C1-C10 perfluoroalkyl group, a C1-C10 alkyl group, or a C1-C1 The functional group is selected from the group of functional groups consisting of an 0 alkenylamino group, an alkenylsulfonic acid group having 1 to 10 carbon atoms, a perfluoroalkenyl group having 1 to 10 carbon atoms, and an alkenyl group having 1 to 10 carbon atoms. Each of these functional groups may have at least one selected from the group consisting of at least one functional group selected from the aforementioned group of functional groups, an aromatic ring, a heterocycle, an oxygen atom, a sulfur atom, a nitrogen atom, a fluorine atom, a chlorine atom, a bromine atom, an iodine atom, and a hydrogen atom in its molecular chain. In formula (2), R1, R2, and R3 may each be a primary amine, a secondary amine, a tertiary amine, or a quaternary ammonium cation. However, this excludes the case in formula (II) where R1, R2, and R3 are all amino groups or cations thereof.
[0027] In addition, in a compound represented by formula (II), if one or two of R1, R2, and R3 are amino groups, it falls under the category of an amino group-containing compound as defined herein.
[0028] The copolymer comprises structural units derived from melamine and structural units derived from formaldehyde, as well as, in some cases, structural units derived from melamine derivatives, and structural units derived from amino group-containing compounds having one or two amino groups.
[0029] The amino group-containing compound is not particularly limited, and may have one or two amino groups. An amino group-containing compound having one amino group may be preferred because it can effectively suppress three-dimensional crosslinking. Furthermore, an amino group-containing compound having one amino group may be preferred because it can form a linear portion while suppressing three-dimensional crosslinking.
[0030] Examples of amino group-containing compounds having one amino group include compounds in formula (II) where one of R1, R2, and R3 is an amino group. Examples of amino group-containing compounds having two amino groups include urea. Examples of such compounds include compounds in formula (II) where two of R1, R2, and R3 are amino groups. Such compounds are not particularly limited, but examples include benzoguanamine.
[0031] In copolymers, the ratio of structural units derived from melamine, structural units derived from formaldehyde, and structural units derived from amino group-containing compounds having one or two amino groups is not particularly limited. From the viewpoint of suppressing three-dimensional crosslinking and accelerating the oxygen reduction reaction activity by the catalytic metal, it is sometimes preferable that the ratio of the amount of substance (molar ratio) of structural units derived from the amino group-containing compound to the structural units derived from melamine is 1.0 or less. If it exceeds 1.0, the promotion effect of the catalytic metal's oxygen reduction reaction activity by the copolymer as a nitrogen-containing organic compound tends to decrease due to the suppression of three-dimensional crosslinking. Note that the above molar ratio is equivalent to the ratio of the amount of substance of the amino group-containing compound as a monomer to the amount of substance of the melamine monomer used in the synthesis of the copolymer being 1.0 or less.
[0032] The copolymer may have structural units derived from additional monomers in addition to the structural units described above. For example, the copolymer may contain structural units derived from thiocyanuric acid. Examples of thiocyanuric acid compounds include thiocyanuric acid and derivatives of thiocyanuric acid. Examples of cyanuric acid compounds include cyanuric acid and derivatives of cyanuric acid.
[0033] These copolymers are obtained by reacting melamine, formaldehyde, and an amino group-containing compound under polymerization conditions. For example, conditions similar to those for the polymerization of melamine and formaldehyde can be used. The degree of polymerization and molecular weight of the copolymer are not specifically limited. The presence of the copolymer in the modified layer allows for strong adsorption onto the catalyst metal, improving adsorption stability. The degree of polymerization of the copolymer may be in the range of 1 to 10000.
[0034] Examples of such copolymers include copolymers of melamine, formaldehyde, and urea as monomers (addition reaction products), and copolymers of melamine, formaldehyde, and benzoguanamine as monomers (condensates).
[0035] [ka] [ka]
[0036] Such resins can be synthesized or commercially available to those skilled in the art. Examples include the Uban® series manufactured by Mitsui Chemicals, Inc. and the Epostor® series manufactured by Nippon Shokubai Co., Ltd.
[0037] The copolymer content in the catalyst is not particularly limited. For example, the copolymer content (or total mass including other copolymers) relative to the mass of the carrier supporting the catalyst metal can be 1.0% by mass or more and 15% by mass or less.
[0038] Here, the mass of the copolymer is determined by extracting the copolymer from the catalyst and measuring the copolymer by chromatography such as HPLC or GC. The mass of the support can be determined by the following method: After removing the copolymer and organic compounds such as binders from the catalyst by solvent separation, the support bearing the remaining catalyst metal can be obtained, and the mass of the support can be measured from the remaining portion after the support has been burned off by calcination. Mass spectroscopy, NMR, IR, UV, etc., can be used as appropriate for identifying the copolymer and support.
[0039] (Binder) The catalyst may also contain a binder. The binder is a polymer electrolyte, for example, an ion exchange group such as an acidic functional group or a basic functional group. Polymer electrolytes are sometimes called electrolytes, ionsomers, or ionsomers. Examples of acidic functional groups include sulfonic acid and phosphoric acid. Examples of basic functional groups include quaternary ammonium cations. The binder may be a perfluorocarbon sulfonic acid polymer, an anion exchange polymer, or a polymer mainly composed of polyether ether ketone and polybenzimidazole.
[0040] The binder content in the catalyst is not particularly limited; it is sufficient as long as it can form a modification layer on the catalyst metal. For example, the ratio of binder mass to support mass can be between 70% and 115% by mass. The support mass is as previously explained. The binder mass is determined by extracting the binder from the catalyst and measuring its mass. For binder identification, mass spectrometry, NMR, IR, UV, etc., can be used as appropriate.
[0041] As previously described, the catalyst can take the form of a catalyst ink, and after the application of the catalyst ink, it can take the form of a catalyst layer. The formation of the catalyst ink and catalyst layer will be described below.
[0042] (Catalyst ink preparation) First, predetermined amounts of a catalyst metal-supported carrier (catalyst metal-supported carrier), copolymer, binder, and solvent are added to a container, and these are stirred using a stirrer to prepare the catalyst ink. The type of solvent is not particularly limited, and any liquid can be used. For example, alcohol or a mixed solution of at least one alcohol and water can be used. Examples of alcohols include methanol, diacetone alcohol, ethanol, 1-propanol, 2-propanol, tert-butyl alcohol, ethylene glycol, and propylene glycol.
[0043] The agitator is not particularly limited, and various known agitators can be used as appropriate. Examples include ultrasonic homogenizers, jet mills, ball mills such as bead mills, high-shear mills, film mixers, etc. The stirring conditions, such as stirring speed, stirring time, and rotation speed, are not particularly limited and can be set as appropriate.
[0044] After stirring, perform vacuum degassing and let it stand for one day. There is no limit to the standing time; it can be set as desired. It is also possible to use the product without standing. Furthermore, vacuum degassing may be performed again.
[0045] (Fabrication of the catalyst layer) The prepared catalyst ink is coated onto a predetermined substrate, and the solvent is removed after coating. For example, the catalyst ink is coated onto the substrate, the coated catalyst ink is heated, and the solvent is dried and removed.
[0046] The substrate is not particularly limited, but examples include polytetrafluoroethylene (PTFE), an electrolyte membrane having ion exchange groups, a gas diffusion layer (GDL) composed of carbon fibers or metal fibers, and a gas diffusion layer composed of carbon fibers or metal fibers having a microporous layer (MPL).
[0047] The coating method can be any method that allows for uniform coating of the catalyst ink onto the substrate, and examples include die coating, spin coating, screen printing, doctor blade coating, squeegee coating, spray coating, and applicator coating. The heating rate and heating time can be appropriately set depending on the type of solvent, etc. The removal rate may also be increased by degassing simultaneously with heating. The coating film thickness may be 5 to 30 μm, and the platinum content may be 0.1 to 0.6 mg / cm². -2 The coating may be applied in such a way that it satisfies the requirements.
[0048] (catalyst layer) This specification provides an oxygen-evolving catalyst layer or an oxygen-reduction reaction catalyst layer containing the catalyst. Since the oxygen reduction reaction of the catalyst metal is reversible, a fuel cell is also provided that has this catalyst layer as a cathode (oxygen-reduction catalyst layer). The fuel cell is, for example, a PEFC. In such a fuel cell, a decrease in the power generation efficiency of the fuel cell due to the deposition of the modification layer is avoided or suppressed. The configuration of the fuel cell other than the cathode is well known to those skilled in the art.
[0049] Furthermore, a water electrolysis system is also provided that includes a catalyst layer containing the catalyst as an anode (oxygen evolution reaction catalyst layer). In such a water electrolysis system, a decrease in the water production efficiency of the water electrolysis device due to the deposition of the modified layer is avoided or suppressed. The components of the water electrolysis system other than the anode are well known to those skilled in the art. [Examples]
[0050] The following describes embodiments that embody the disclosures of this specification. These embodiments are illustrative and not intended to limit the scope of the disclosure. [Examples]
[0051] A catalyst metal particle-supported carrier, in which platinum particles (particle size: 3-4 nm) as a catalyst metal are supported on a carrier (acetylene black), a copolymer with the composition shown in the table below, perfluorocarbon sulfonic acid as a binder, and a water-alcohol mixture as a solvent were added to a container in predetermined amounts. The mass of the copolymer relative to the mass of the carrier was set to 0.03.
[0052] These materials were mixed and stirred using a stirrer (homogenizer, film mixer) to prepare catalyst inks of Examples 1 to 4, which contained an oxygen reduction catalyst.
[0053] Comparative Example 1's catalyst ink was prepared in the same manner as in Example 1, except that it did not contain a copolymer. Comparative Example 2's catalyst ink was prepared in the same manner as in Example 1, except that the copolymer contained melamine. Comparative Example 3's catalyst ink was prepared in the same manner as in Example 1, except that it contained a melamine-formaldehyde polymer (melamine resin) instead of the copolymer.
[0054] A catalyst ink, which had undergone degassing treatment as appropriate, was coated onto a substrate. After coating, the catalyst ions were heated to dry and remove the solvent, thereby creating a catalyst layer.
[0055] Next, each of the fabricated catalyst layers was prepared as a cathode catalyst layer, a perfluorocarbon sulfonic acid polymer (Nafion NR211, EW:1100, manufactured by Chemors) as the electrolyte membrane, and a platinum-supported carbon catalyst (TEC10E50E, manufactured by Tanaka Kikinzoku Kogyo) as the anode catalyst layer. The electrolyte membrane was sandwiched between the cathode catalyst layer and the anode catalyst layer. The cathode catalyst layer, electrolyte membrane, and anode catalyst layer were thermocompressed together under heating (130°C) and pressurizing (3 MPa) conditions. A gas diffusion layer made of carbon fibers (GDL 22BB, manufactured by SGL) was placed outside the cathode catalyst layer and the anode catalyst layer to fabricate a membrane electrode assembly (MEA) (electrode section: 1 cm × 1 cm).
[0056] [Table 1]
[0057] Next, the current-voltage characteristics were measured using the fabricated MEA as a single cell under low humidity conditions (30%RH) and high humidity conditions (80%RH). The measurement conditions were as follows: Sweep speed: 20mA / s (anode sweep), cell temperature: 80℃, pressure: 150kPa_ABS, cathode gas type: air, cathode gas flow rate: 2.0L / min. Using the fabricated MEA, a current-voltage of 3.2A / cm² was measured. 2 The cell voltage was measured at 3.2 A / cm. 2 The cell voltage in this region is dominated by the concentration overpotential, which indicates the transport characteristics of the reaction substrate, and is a region where the claim for supplying the reaction substrate to the catalyst surface is important. A high cell voltage in this region indicates excellent reaction substrate transport characteristics and thus excellent battery characteristics. 3.2 A / cm for Comparative Example 1 2 The difference in cell voltages is shown in Table 1.
[0058] As shown in Table 1, Example 1, which used a copolymer containing urea as the amino group-containing compound in a melamine moiety ratio of 1.0 or less, showed the highest cell voltage. Example 3, which used a copolymer containing benzoguanamine as the amino group-containing compound in a melamine moiety ratio of 1.0 or less, showed the next highest cell voltage.
[0059] In contrast, in Example 2, where the amount of urea used was less than 1.0 in Example 1, and in Example 4, where the amount of benzoguanamine used was less than 1.0 in Example 3, the cell voltage decreased. Furthermore, Examples 1 to 4 showed higher cell voltages than Comparative Examples 2 and 3, which used melamine and melamine resin, respectively, as the organic nitrogen compound.
[0060] From the above, it was found that using melamine-formaldehyde copolymers containing structural units derived from amino group-containing compounds such as urea and benzoguanamine as monomers is effective in improving battery performance. In other words, it was found that such copolymers facilitate the supply of reaction substrates to the catalyst metal and exhibit a catalytic activity-enhancing effect due to the copolymer as an organic nitrogen compound. Furthermore, it was found that by setting the molar ratio of these amino group-containing compounds to melamine in the copolymer to 1.0 or less, the supply characteristics of the reaction substrate can be improved even more effectively, thereby exhibiting a catalytic activity-enhancing effect.
Claims
1. An oxygen reduction catalyst, A catalyst metal having oxygen reduction reaction activity, A modified layer containing a copolymer or cation thereof having structural units derived from melamine, structural units derived from formaldehyde, and structural units derived from one or two amino group-containing compounds, An oxygen reduction catalyst equipped with the following features.
2. The oxygen reduction catalyst according to claim 1, wherein the amino group-containing compound is urea.
3. The oxygen reduction catalyst according to claim 1, wherein the amino group-containing compound is benzoguanamine.
4. The oxygen reduction catalyst according to claim 1, wherein the copolymer has a substance amount of the amino group-containing compound relative to the melamine of 1.0 or less.
5. A cathode for a fuel cell comprising the oxygen reduction catalyst according to any one of claims 1 to 4.
6. A fuel cell comprising the cathode described in claim 5.
7. An anode for a water electrolysis system comprising the oxygen reduction catalyst according to any one of claims 1 to 4.
8. A water electrolysis system comprising the anode described in claim 7.
Citation Information
Patent Citations
Catalyst
JP2024011754A